Essentials of SGLT2 Inhibitors in Diabetes - Fisher, Miles; McKay, Gerard (Springer International Publishing : Imprint: Adis, 2017)
Written by experts in the field, this clinical handbook explores the novel SGLT2 drug class for the treatment of diabetes. This book includes evidence-based guidelines, major clinical trials, and a discussion of treatment options currently available, as well as those currently in development. Essentials of SGLT2 Inhibitors is an ideal educational resource for busy medical professionals who need to stay up-to-date with diabetes treatment advances in order to provide the best possible clinical care for their patients.